Identification of large-for-gestational age fetuses using antenatal customized fetal growth charts: Can we improve the prediction of abnormal labor course?. (May 2020) - Dall'Asta, Andrea; Rizzo, Giuseppe; Kiener, Ariane; Volpe, Nicola; Di Pasquo, Elvira; Roletti, Enrica; Mappa, Ilenia; Makatsariya, Alexander; Maruotti, Giuseppe Maria; Saccone, Gabriele; Sarno, Laura; Papaccio, Marta; et al.
Abstract: Introduction: Fetal overgrowth is an acknowledged risk factor for abnormal labor course and maternal and perinatal complications. The objective of this study was to evaluate whether the use of antenatal ultrasound-based customized fetal growth charts in fetuses at risk for large-for-gestational age (LGA) allows a better identification of cases undergoing caesarean section due to intrapartum dystocia. Material and methods: An observational study involving four Italian tertiary centers was carried out. Women referred to a dedicated antenatal clinic between 35 and 38 weeks due to an increased risk of having an LGA fetus at birth were prospectively selected for the study purpose. The fetal measurements obtained and used for the estimation of the fetal size were biparietal diameter, head circumference, abdominal circumference and femur length, were prospectively collected. LGA fetuses were defined by estimated fetal weight (EFW) >95th centile either using the standard charts implemented by the World Health Organization (WHO) or the customized fetal growth charts previously published by our group. Patients scheduled for elective caesarean section (CS) or for elective induction for suspected fetal macrosomia or submitted to CS or vacuum extraction (VE) purely due to suspected intrapartum distress were excluded. The incidence of CS due to labor dystocia was compared between fetuses with EFW >95th centile according WHO or customized antenatal growth charts. Results: Overall, 814 women were eligible, however 562 were considered for the data analysis following the evaluation of the exclusion criteria. Vaginal delivery occurred in 466 (82.9 %) women (435 (77.4 %) spontaneous vaginal delivery and 31 (5.5 %) VE) while 96 had CS. The EFW was >95th centile in 194 (34.5 %) fetuses according to WHO growth charts and in 190 (33.8 %) by customized growth charts, respectively. CS due to dystocia occurred in 43 (22.2 %) women with LGA fetuses defined by WHO curves and in 39 (20.5 %) women with LGA defined by customized growth charts (p 0.70). WHO curves showed 57 % sensitivity, 72 % specificity, 24 % PPV and 91 % NPV, while customized curves showed 52 % sensitivity, 73 % specificity, 23 % PPV and 91 % NPV for CS due to labor dystocia. Conclusions: The use of antenatal ultrasound-based customized growth charts does not allow a better identification of fetuses at risk of CS due to intrapartum dystocia.